2010
DOI: 10.1093/cvr/cvq321
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of soluble vascular endothelial growth factor receptor-1 prevents angiogenesis in hypertrophied myocardium

Abstract: Up-regulation of the soluble VEGFR-1 in pressure-loaded myocardium prevents capillary growth by trapping VEGF. Inhibition of sVEGFR-1 released sufficient VEGF to induce angiogenesis and preserved contractile function. These data suggest sVEGFR-1 as possible therapeutic targets to prevent heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…Furthermore, mesothelin levels were previously found to be higher in patients with impaired renal function, which is in accordance with our results [29]. Angiogenin and VEGFR1, which had the highest levels in young patients, were linked to angiogenesis and revascularization [30][31][32][33]. Both markers are pathophysiologically involved in vascular repair and cardiac remodeling, both of which are etiological factors for the development of HFrEF.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, mesothelin levels were previously found to be higher in patients with impaired renal function, which is in accordance with our results [29]. Angiogenin and VEGFR1, which had the highest levels in young patients, were linked to angiogenesis and revascularization [30][31][32][33]. Both markers are pathophysiologically involved in vascular repair and cardiac remodeling, both of which are etiological factors for the development of HFrEF.…”
Section: Discussionsupporting
confidence: 92%
“…While the homeostatic role of VEGF-A in the myocardium has been well established 39 and inhibition of VEGF signaling has been shown to trigger myocardial hibernation, 39 upregulation of the expression of soluble growth factor receptor 1 (sVEGFR1 or sFlt-1) has been shown to prevent angiogenesis in the hypertrophied myocardium. 73 We found that the sFlt-1 protein concentration in the serum and RV tissues trended toward being increased in SuHx rats (Figs. 1I, 2G).…”
Section: Discussionmentioning
confidence: 71%
“…7,8 In clinical settings, plasma levels of sFlt-1 are not only directly correlated with the severity of heart failure but also strongly associated with poor outcomes in patients with heart failure.…”
Section: Suppressed Production Of Soluble Fms-like Tyrosine Kinase-1 mentioning
confidence: 99%
“…2 Recently, it has been shown that sFlt-1 is implicated in the pathogenesis of cardiovascular disease. [3][4][5][6][7][8][9][10] In a series of previous studies, 3,4,11 we demonstrated that sFlt-1 production is decreased in patients with chronic kidney disease (CKD) and in an experimental model of renal failure 3 and that decreased sFlt-1 production correlates with the development of atherosclerosis and cardiovascular events. 3,4 Furthermore, previous reports showed that the gene delivery of sFlt-1 suppresses atherosclerosis development in an animal model, 5 and the increase in sFlt-1 levels induced by atorvastatin treatment is associated with improvement of ventricular Seno et al sFlt-1 and Heart Failure 679 function in patients with acute coronary syndrome.…”
mentioning
confidence: 93%